LUZP1 Controls Cell Division, Migration and Invasion Through Regulation of the Actin Cytoskeleton - Bozal-Basterra, Laura; Gonzalez-Santamarta, María; Muratore, Veronica; Martín-Martín, Natalia; Ercilla, Amaia; Rodríguez, Jose A.; Carracedo, Arkaitz; Sutherland, James D.; Barrio, Rosa (Frontiers in Cell and Developmental Biology, 2021)
LUZP1 is a centrosomal and actin cytoskeleton-localizing protein that regulates both ciliogenesis and actin filament bundling. As the cytoskeleton and cilia are implicated in metastasis and tumour suppression, we examined roles for LUZP1 in the context of cancer. Here we show that LUZP1 exhibits frequent genomic aberrations in cancer, with a predominance of heterozygous loss. Furthermore, we demonstrate that CRISPR/Cas9-mediated loss of Luzp1 in mouse fibroblasts promotes cell migration and invasion features, reduces cell proliferation, and increases cell apoptosis, centriole numbers, and nuclear size while altering the actin cytoskeleton. Loss of Luzp1 also induced changes to ARP3 and phospho-cofilin ratios, suggesting regulatory roles in actin polymerization, beyond its role in filament bundling. Our results point to an unprecedented role for LUZP1 in the regulation of cancer aggressiveness through the control of actin cytoskeleton.